Association between opioid use disorder and fractures: a population‐based study - Hsu, Wen‐Yu; Lin, Cheng‐Li; Kao, Chia‐Hung (Addiction (Abingdon, England), 2019)
Aims To test whether fractures and osteoporosis are more prevalent among patients with opioid use disorder (OUD) than patients without OUD in Taiwan. Design We conducted a retrospective cohort study using data from the National Health Insurance Research Database (NHIRD) in Taiwan. Setting Taiwan. Participants The number of adult patients with OUD and without OUD was 3695 and 14 780, respectively. We established both cohorts from 1 January 1998 to 31 December 2011 to observe the incidence of fracture. The occurrence of fracture was followed‐up until the end of 2011. Measurements The primary measure was incidence of fracture. The relative risk of fracture was estimated using the Cox proportional hazard model after adjusting for age, sex, index year and comorbidities. Comorbidities included diabetes mellitus, hyperlipidemia, stroke, chronic obstructive pulmonary disease, heart failure, alcohol‐related illness, osteoporosis, end‐stage renal disease, obesity and rheumatoid arthritis, using the International Classification of Diseases, 9th revision, clinical modification. Findings Patients with OUD were 4.13 times more likely to suffer fractures than patients without OUD [incidence rate (IR) per 1000 person‐years = 23.0 versus 5.47, adjusted hazard ratio (HR) = 3.74, 95% confidence interval (CI) = 3.27–4.29]. Compared with the control group, the risk of fracture was higher among the patients with OUD. Risk of fracture was higher in male elderly patients with diabetes mellitus, alcohol‐related illness or osteoporosis. The cumulative incidences of fracture over 14 years of patients with OUD and without OUD differed significantly. Conclusions Taiwanese patients with opioid use disorder appear to have a higher adjusted hazard ratio for fracture than Taiwanese patients without opioid use disorder.